KOMPOSISI POHON DI BUKIT ACE KELURAHAN GUNUNG SARIK KECAMATAN KURANJI PADANG - Rizki, Rizki; Safitri, Elza (Sainstek : Jurnal Sains dan Teknologi, 2016)
The existence of trees in a region could be threatened because of their good forest damage due to natural factors such as fires and landslides, as well as human activities mainly due to illegal logging. This study aims to determine the composition of a tree in Bukit Ace in the sub Kuranji Padang. In this study using a survey method using a combination of methods to make trransek track and map examples. Transects were observed along the 20 meter by 10 mapped sample with a size of 10x10 meter Analysis of vegetation cover density, frequency, dominance, importance and diversity index. Based on research conducted at the Mount Ace Village of Mount Sarik District of Kuranji Padang, tree composition consists of 13 species and 172 individuals where species of trees by people who at least is Anacardium ocidentale ie 3 people whereas species with people most is Xerospermum intermedium (31 people) , Important values ranging between 6.107% - 60.327%, of tree species that have significant value the highest is Xerospermum intermedium is 60.327% and tree species with important value lows are Evodia malayana namely 6.107%, while based on diversity index of forest in Bukit Ace classified as being abundant with value ID 2,351.